Intraoperative Wound Lavage System for Deep Neck Infection: A Retrospective Cohort Study - Abdul-Hadi, Soraya; Perez, Francis Beauchamp; Pascual-Marrero, Jeamarie (International Archives of Otorhinolaryngology, 2023)
Introduction Multiple solutions are currently used to cleanse a deep neck infection (DNI), and a variety of devices are available to deliver wound irrigation solutions. An essential difference between these devices is the pressure that the irrigation solution exerts over the wound tissue.Objective To compare low-pressure and high-pressure irrigation delivery systems for wound cleansing in DNI.Methods we designed a retrospective cohort study and reviewed the medical records of patients operated on due to DNI from June 2016 to December 2017 at our institution. One cohort included patients treated with an intraoperative irrigation method that exerts low pressure over the irrigated tissue, and the other cohort, to a system capable of generating higher pressure. The Pearson Chi-squared test was used to analyze the data.Results A total of 42 patients whose ages ranged from 16 months to 72 years were included. The low-pressure irrigation system was used in 18 patients, and the high-pressure system was used in 24 patients. No statistical differences were observed regarding the irrigation methods, the complexity of the DNI, and the overall outcomes.Conclusions The present is the first study in which low- and high-pressure systems for wound lavage were evaluated in the treatment of DNI. When comparing these methods, we did not find one to be superior to the other; however, the additional cost associated with the high-pressure devices may not justify their in head and neck procedures.
Keywords: debridement; infection; lavage; neck; surgical wound; deep neck infection